Aes Based Blood Bank System Using Cloud Techniques (Journal of Pharmaceutical Negative Results, 2023)
Blood donation is required for saving human lives. Blood donor needs to check blood bank or donation camp for giving blood donation or blood booking. Blood donor may have doubt whether their personal data and medical histories are safely deposited and protected. For this purpose, proposed work uses cloud techniques to develop an online blood bank system and applying Advanced Encryption Standard (AES) algorithm for database security and encryption. Proposed system maintains central repository holding various blood deposits accessible along with related particulars accommodated on a cloud server. These particulars contain type of blood group, area of storage, date and location etc., This information support in maintaining and monitoring the deposits of blood. Proposed AES based blood bank system using cloud techniques is an online system that consents handlers to check whether the essential blood deposits of a particular group are available in the blood bank capably using a cloud server. Additionally, the system also has extra features such as patient details, blood booking and even the need for a certain blood group is posted on the website to find available donors for a blood emergency. Apart from this, system includes the concepts of database encryption using AES Algorithm to make sure that the security and confidentiality of users’ information. This will help us keep their donation records protected from any threats from individuals with potentially malicious intentions, or any unforeseen hazards to the security of the data. Main aim of the proposed work is to reduce the time required to deliver obligatory blood to the needy in cases of emergency. AES Algorithm will help us keep their donation records protected from any threats from individuals with potentially malicious intentions, or any unforeseen hazards to the security of the data. This AES Based blood bank system using Cloud techniques is an online system that helps in handling several blood bank procedures successfully.